2016
DOI: 10.1177/0271678x16653615
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative longitudinal imaging of activated microglia as a marker of inflammation in the pilocarpine rat model of epilepsy using [11C]-(R)-PK11195 PET and MRI

Abstract: Inflammation may play a role in the development of epilepsy after brain insults. [11C]-(R)-PK11195 binds to TSPO, expressed by activated microglia. We quantified [11C]-(R)-PK11195 binding during epileptogenesis after pilocarpine-induced status epilepticus (SE), a model of temporal lobe epilepsy.Nine male rats were studied thrice (D0-1, D0 + 6, D0 + 35, D0 = SE induction). In the same session, 7T T2-weighted images and DTI for mean diffusivity (MD) and fractional anisotropy (FA) maps were acquired, followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…To be considered a useful biomarker for studying a pathologic condition, TSPO expression has to be altered during the disease. In this regard, longitudinal in vivo TSPO PET imaging during epileptogenesis in the lithium+pilocarpine SE rat model revealed increased microglia activation in epileptogenesis‐associated brain regions within days from the acute insult and peaking 1–2 weeks after SE . This evidence was replicated in the systemic and focal intrahippocampal kainic acid post‐SE rodent models and is in accordance with histologic assessment of microglia activation and the time course of neuroinflammatory markers measured with histologic or biochemical techniques.…”
Section: Imaging Glia By Positron Emission Tomography (Pet) As a Biomsupporting
confidence: 72%
“…To be considered a useful biomarker for studying a pathologic condition, TSPO expression has to be altered during the disease. In this regard, longitudinal in vivo TSPO PET imaging during epileptogenesis in the lithium+pilocarpine SE rat model revealed increased microglia activation in epileptogenesis‐associated brain regions within days from the acute insult and peaking 1–2 weeks after SE . This evidence was replicated in the systemic and focal intrahippocampal kainic acid post‐SE rodent models and is in accordance with histologic assessment of microglia activation and the time course of neuroinflammatory markers measured with histologic or biochemical techniques.…”
Section: Imaging Glia By Positron Emission Tomography (Pet) As a Biomsupporting
confidence: 72%
“…TSPO PET signal is markedly upregulated in neurodegenerative and neuroinflammatory diseases including multiple sclerosis (Vowinckel et al , 1997; Versijpt et al , 2005; Oh et al , 2011; Rissanen et al , 2014; Datta et al , 2017 b ), Alzheimer’s disease (Edison et al , 2008; Yasuno et al , 2008), Parkinson’s disease (Ouchi et al , 2005), viral encephalitis (Banati et al , 1999; Cagnin et al , 2001), amyotrophic lateral sclerosis (Turner et al , 2004 a ), Huntington’s disease (Meßmer and Reynolds, 1998) and frontotemporal dementia (Cagnin et al , 2004) and thus has become recognized as a marker of in vivo neuroinflammation (Banati et al , 2000; Venneti et al , 2006; Colasanti et al , 2014). A limitation of these applications has been uncertainty regarding the interpretation of increased signal; many of the studies have widely assumed that increased signal reflects activated microglia, while ignoring the potential contributions of astrocytes and other cell types (Groom et al , 1995; Vowinckel et al , 1997; Banati et al , 2000; Cagnin et al , 2001; Debruyne et al , 2003; Gerhard et al , 2003, 2004, 2006 a , b ; Henkel et al , 2004; Turner et al , 2004 b ; Tai et al , 2007; Tomasi et al , 2008; Venneti et al , 2009; Politis et al , 2015; Ghadery et al , 2017; Yankam Njiwa et al , 2017). Although recent studies using animal models of neurodegenerative diseases have shown astrocytic TSPO (Maeda et al , 2007; Rojas et al , 2007; Arlicot et al , 2008; Ji et al , 2008; Mattner et al , 2011; Lavisse et al , 2012 b ; Daugherty et al , 2013; Dickens et al , 2014; Wang et al , 2014; Lavisse et al , 2015; Sérrière et al , 2015; Domene et al , 2016; Israel et al , 2016; Nguyen et al , 2018), only a few have examined astrocytic expression of TSPO in the human CNS (Kaunzner et al , 2019), and these descriptions have been qualitative rather than quantitative (Cosenza-Nashat et al , 2009; …”
Section: Introductionmentioning
confidence: 99%
“…Previously described methods for HPLC analysis of PK11195 were overall similar to the method proposed in this study, but there was a large range of HPLC mobile phases and UV wavelengths used for PK11195 elution and detection. The UV light wavelengths ranged from 254 nm to 310 nm, and organic solvent:water ratio of the mobile phase ranged between 30:70 to 80:20 [[22], [23], [24]]. Using our chromatographic system, and after testing a wide range of UV wavelengths, we concluded that the optimal wavelength to detect PK11195 in biological samples was 331 nm (data not shown).…”
Section: Discussionmentioning
confidence: 94%